2007
DOI: 10.1177/1078155207080802
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between mercaptopurine and milk

Abstract: Mercaptopurine is a purine analog used for acute lymphoblatic leukemia and chronic myelogenous leukemias. Since it is inactivated by xanthine oxidase (XO), concurrent intake of substances containing XO may potentially reduce bioavailability of mercaptopurine. Cow's milk is known to contain a high level of XO. In vitro and in vivo data suggest that concurrent intake of cow's milk may reduce the bioavailability of mercaptopurine. This interaction may be clinically significant. Therefore most patients should try … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Therefore most patients should try to separate the timing of taking mercaptopurine and drinking milk. 75 Tamoxifen is a successful anti-tumor agent. If taken with sesame seeds, it negatively interferes with tamoxifen in inducing regression of established MCF-7 tumor size but beneficially interacts with tamoxifen on bone in ovariectomized athymic mice.…”
Section: Antitumor Drugsmentioning
confidence: 99%
“…Therefore most patients should try to separate the timing of taking mercaptopurine and drinking milk. 75 Tamoxifen is a successful anti-tumor agent. If taken with sesame seeds, it negatively interferes with tamoxifen in inducing regression of established MCF-7 tumor size but beneficially interacts with tamoxifen on bone in ovariectomized athymic mice.…”
Section: Antitumor Drugsmentioning
confidence: 99%
“…Several small studies,56,59,192,193 although not all,194–196 have demonstrated reduced bioavailability for both MTX and 6MP, when the drugs are administered together with food, and for 6MP specifically with milk due to its content of xanthine oxidase 197. Accordingly, nearly all study groups recommend 6MP and MTX to be taken without concomitant ingestion of food 48.…”
Section: Food and Maintenance Therapymentioning
confidence: 99%
“…[7][8][9] When patients relapse, the maintenance component of treatment has probably failed for some reasons. [5] Potential determinants of adequate systemic 6-MP exposure include pharmacogenetics, [8,10,11] bioavailability, [12][13][14][15] and adherence to daily oral administration. [16][17][18] was signed along with the questionnaires asked and blood samples taken all in the same visit.…”
Section: Discussionmentioning
confidence: 99%